The threat : a novel - Poyer, David (Poyer, David. Tales of the modern Navy., 2006)
Dan Lenson, joins the National Security Council staff at the White House, where he runs into an unconvincing presidential assassination plot. Robert De Bari, despised by the military for his failure to serve in Vietnam and is known for a roving eye, occupies the Oval Office after the first Gulf War. Lenson assumes a host of tasks, from antidrug duty for the NSC to being the president's military aide carrying the legendary briefcase with its nuclear launch codes. As astute as Lenson is, he proves to be naive as forces that want De Bari replaced by the vice president manipulate him.